Indonesia: Problem Encountered in Some Unresolved Boundaries and the Outermost Island Issues - Agoes., Etty R. (Indonesian Journal of International Law, 2011)
Within the framework of national integrity the ocean possesses two key aspects that is, of security and prosperity. The demarcation of the outer limits of national mari- time territory and jurisdiction including delimitation of boundaries with neighboring countries will provide a legal basis for a number of marine activities such as defense, fisheries, navigation, seabed and subsoil exploration and exploitation, marine tourism and others. Boundary issues for Indonesia, whether on land, at sea even in the air, have always been a matter of national priority. At present, Indonesia still have some unresolved boundary delimitation with its neighboring countries. The completion of the boundary of Indonesia's maritime territory and jurisdiction shall also ascertain Indonesia's maritime authority as an independence and sovereign state, provides security for the whole nation, and the fulfillment of strong economy through the utilization of marine resources. This paper would examine various factors affecting the delimitation of maritime boundaries, legal status of the boundary of maritime territory and jurisdiction of Indonesia, the out- ermost islands issues, and boundary delimitation process.